Cuboid-Navicular Tarsal Coalition in an Adolescent Female Athlete: A Case Report. Issue 4 (October 2015) - Kamiya, Tomoaki; Watanabe, Kota; Teramoto, Atsushi; Yamashita, Toshihiko
Abstract : Case: A fourteen-year-old female shot-putter developed midfoot pain with activity that initially responded to nonoperative care. However, the symptoms subsequently returned and became persistent. Advanced imaging demonstrated a fibrous cuboid-navicular tarsal coalition. Surgical resection of the tarsal coalition was performed when the patient was seventeen years old, and she returned to sports activities postoperatively with no pain. Conclusion: Although fibrous cuboid-navicular tarsal coalition is a very rare condition, it should be considered as one cause of persistent midfoot pain in an adolescent athlete. Surgical resection of the tarsal coalition can lead to a resolution of symptoms.